Unmaking the commons: collective action, property rights, and resource appropriation among (agro-)pastoralists in eastern Ethiopia - Beyene, Fekadu; Korf, Benedikt (University of Pennsylvania Press, 2011)
This chapter explores these dynamics in the pastoralist commons of eastern Ethiopia. We study current practices of managing water and pasture resources of pastoralist and agropastoralist groups at three sites in Somali Region, Ethiopia. We investigate how changing property rights regimes affect incentives to participate in collective action. Our studies suggest that in the process of unmaking the commons, benefit streams to significant water and pasture resources are individualized, whereas social duties to manage communal resources through collective action are externalized. Such patterns disturb customary practices of reciprocal resource-sharing arrangements, which in the past have been instrumental in managing risk in pastoralist livelihoods and unraveling intraclan social obligations that have helped the poor. With regard to the conceptual framework presented in Chapter 2, this study illustrates how relationships between elements of the initial context and the action arena can lead to the emergence of patterns of interaction that have negative implications for the well-being of people, especially poorer, less powerful individuals in society.